The cull (2023), volume 1 ebook - Thompson, Kelly (The Cull (2023), 2024)
Eisner-winning writer KELLY THOMPSON re-teams with superstar artist MATTIA DE IULIS for their first creator-owned work together—a dark tale of five friends setting off in the middle of the night to shoot a short film on a forbidden rock near their small coastal town the summer before they all go their separate ways. But they're not really there to shoot a film. One of them has lied. And that lie will change EVERYTHING. Collects THE CULL #1-5